Social Behavior of Early Childhood Through Playing Beams Activity - Mila Karmila; Muhtarom Muhtarom (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The focus of this research is to explore and describe the ability of children's social behavior through playing beams. This research used qualitative descriptive method, which was used to examine the children's natural activity when playing beams. This research was conducted at the Child Care Center of Child Vocational Education (TPA PENA PRIMA) with the subject as many as 4 early childhood children aged 3-4 years. The data collection method used was observation, documentation and interviews. Data analysis techniques included collecting data, selecting data, presenting data and concluding. The findings of the research showed that there were differences in social behavior in each child in playing beams activities such as imitation, competition, cooperation, sympathy, empathy, social support, sharing, and familiar behavior. This research shows that playing activities and peer roles are essential for optimizing the children's social behavior. Schools are expected to provide supporting facilities for beam playing activities.